A NEW SYSTEMATIC APPROACH FOR WAREHOUSE MANAGEMENT SYSTEM EVALUATION - (:unkn) unknown (UNIV OSIJEK, TECH FAC, 2016)
Warehouse management is one of the most important legs in supply chain operations and production management. To support that warehouse execution, a warehouse management system is required. Many warehouses have used various methods to handle this difficult and time consuming evaluation process. The purpose of this paper is to provide a decision support model to make a careful evaluation of warehouse management system. Purchasing an appropriate warehouse management system in a supply value chain is not an easy decision making and is related to fuzziness and uncertainty, which should be considered as a large number of complex factors in multiple evaluation criteria. A Fuzzy Multi Criteria Decision Making approach is adopted to effectively evaluate warehouse management systems. To provide a practical guidance for other companies a real life framework is presented with an application.
Keywords: ELECTRE; Fuzzy AHP; Fuzzy ANP; Fuzzy Multi Criteria Decision Making; TOPSIS; warehouse management system; DECISION-SUPPORT-SYSTEM; SELECTION; PICKING; DESIGN; OPERATIONS; AHP